A reaction-driven evolving network theory coupled with phase-field fracture to model polymer oxidative aging. (May 2021) - Konica, Shabnam; Sain, Trisha
Abstract: High-temperature oxidation in polymers is a complex phenomenon, driven by the coupled diffusion–reaction process, causing changes in the amorphous network structure and resulting in property degradation. Prolonged oxidation in polymers results in the formation of a coarse, oxide layer on the outer surface and induces spontaneous cracking inside the material. In this paper, we present a chemical reaction-driven evolving network theory coupled with phase-field fracture to describe the effect of oxidation in polymers across different length scales. Guided by the statistical mechanics, the network theory has been introduced to model the reaction induced chain scissions and crosslinking events causing significant changes in the three-dimensional network structure. Further, these microscale events have been considered as the reason behind macroscopic mechanical property degradation, namely oxidative embrittlement. Finally the network theory is coupled with a phase-field fracture to model the macroscale damage initiation and propagation in the polymer under mechanical stress. The specific constitutive forms for all the physical–chemical processes are derived for the coupled system and numerically implemented in finite elements by writing ABAQUS user-defined element (UEL) subroutine. To present the model's capability, various numerical examples with standard fracture geometries have been studied. The simulation results have demonstrated the model's capability of predicting the effect of oxidative aging on the polymer's response.